EVALUATION OF THE BIOLOGICAL ACTIVITY OF WINTER WHEAT PHYTOLECTINS - Pospielov, S.V.; Chebotariova, L.V.; Pospielova, G.D.; Kornienko, A. O. (Scientific Progress & Innovations, 2019)
As a result of experiments it was established that, besides other protein compounds, winter wheat (Triti-cum aestivum L.) contains lectins, which are able to bind reversibly to carbohydrates, oligosaccharides and polysaccharides. Their role at all levels of the living organism organization, communication and signalling processes is proved. Winter wheat phytolectins are involved in the processes of pathogenesis, interaction with free-living nitrogen-fixing bacteria, response to stresses of various nature, etc. In our current research, phytolectins were isolated from winter wheat in the phase of full ripeness (seeds, straw, and chaff) and eval-uated by bio-testing system (germinating watercress seeds) for biological activity in the concentration range of 1.0–10-12 %. As a source of lectin samples, Tsarychanka, Ukrainka Poltavska and Karmeliuk winter wheat varieties were used (bred at Poltava State Agrarian Academy). Evaluation of lectins in seeds revealed a high biological activity of substances in Ukrainka Poltavska variety. Growth stimulation in the test samples in a range of 9.4–57.5 % (relatively to the control) was observed at all dilutions. At lectin concentrations of 1.0–10–8 % (Karmeliuk variety), watercress root growth inhibition by -2.5– -51.3 % was observed in com-parison with the control. The highest inhibition was at dilutions of 0.1–0.01 %. Subsequent diluting to con-centrations of 10-9–10-10 % stimulated the growth of the tested object, up to 37 %. Phytolectins of Tsarychan-ka grains affected the test samples equally at any concentration. At the concentrations of 10-4-10-7 %, root growth activity was the highest (+19.6–80.5 % in comparison with the control). Phytolectins that were iso-lated from straw of Ukrainka Poltavska and Tsarychanka varieties both stimulated (+4.1–51.5 %) and inhib-ited (-1.9 – -33.0 %) watercress root growth, depending on the concentration. Straw proteins of Karmeliuk variety actively stimulated the growth of the test system (+18.2–127.8 % to the control), but inhibited the growth at concentrations of 10-2–10-4 % (-11.6– -69.9% to the control). Lectins isolated from chaff of Ukrainka Poltavska variety caused inhibiting the growth up to -4.8– -40.3 % at most concentration levels. Another activity was observed while testing Tsarychanka chaff lectins. At concentration levels of 10-1–10-4% stimulation of the watercress root growth was up to 30.4–67.9 %, but at further diluting we observed inhibi-tion up to -5.4– -30.3 %. At almost all concentrations (10-2–10-12 %) of Karmeliuk variety chaff agglutinins, the root growth of the watercress was stimulated to 30.1–98.9 %, comparing to the control. Our study con-firms high biological activity of winter wheat phytolectins, their variety specificity. It is important to note that the high activity of substances contained in straw and chaff performs a stimulating function of winter wheat phytolectins.